Om Grundtvigs historiesyn - Michelsen, William (Grundtvig-studier, 1965)
On Grundtvigs View of History By William Michelsen. What gave rise to this article was the chapter “ Verdenshistorie” in dr. Kaj Thaning’s thesis Menneske først—where, in a note, it has been demonstrated that an anecdote about the old Grundtvig, taken from an article by dr. Holger Kjær, has ben inaccurately reproduced in my thesis Tilblivelsen af Grundtvigs historiesyn, p. 43. Sources older than dr. Kjær’s show that on the occasion in question Grundtvig did not speak of world history but of biblical history; dr. Thaning has emphasized the fact that Grundtvig did not use the expression “genfødt” (reborn) but only said that man was destined to receive regeneration and eternal life.— I agree that the latter distinction is essential, from his point of view; from mine it is irrelevant, because both expressions indicate that Grundtvig’s view of history was biblical; the former distinction is relevant, however, inasmuch as the anecdote cannot be used to show that Grundtvig’s view of world history was biblical. But that it was biblical can be attested by many other examples. And since in the periodical Danske Udsyn, 1964, Thaning has made this hypothesis from the introduction to my thesis a direct object of attack, a series of new quotations from Haandbog i Verdens-Historien are adduced in support of it (U S VI, p. 558, 563-64; VII, p. 379-80 and 703). I agree with Thaning that not until 1832 ff. did Grundtvig consider being a man a condition of being a Christian. But I maintain that already in 1810 he protested against any form of “ gnosticism” (U S II, p. 12). The consequences of this protest, however, dawned upon him only very slowly. Accordingly the subtitle of Thaning’s thesis “ Grundtvigs opgør med sig selv” (the heart-searchings of Grundtvig) covers the whole body of his work from 1810 onwards. In my opinion it was Luther who directed Grundtvig away from “ gnosticism” by teaching him to regard the Bible as historical truth. Although the demonstrative emphasis on this point recedes into the background in Haandbog i Verdens-Historien (1833 ff.), it is nevertheless unmistakably there. According to my thesis and its sequel (Den sælsomme forvandling i N. F. S. Grundtvigs liv (1956)) there are two quite distinct reasons for this: 1) All writing of history is conditioned by a minimum of belief in the sources used, including the Bible; and Grundtvig knew this. 2) Grundtvig the historian neither can nor will conceal his Christian faith. From a non-theological viewpoint— that of the historian of ideas— Grundtvig can not, as Thaning maintains, be said to “ sækularisere sit historiesyn” (securalize his view of history) after 1832. I assert that Grundtvig’s personal outlook on life makes itself felt also in his secular historical writings. Already in 1813 Grundtvig had begun to work out a philosophical foundation for his reflections on “ Menneskets Vilkaar” (the conditions of man) (see Værker i Udvalg II and Nordisk tidskrift (1946)). He published some of his thoughts on the matter in the periodical Danne-Virke 1816-19. Interesting preparatory studies exist among his manuscripts. A confrontation of these thoughts with those of the mature Grundtvig of 1832 ff. has not yet been undertaken.